2010
DOI: 10.1063/1.3478551
|View full text |Cite
|
Sign up to set email alerts
|

Time-dependent auxiliary density perturbation theory

Abstract: The recently developed auxiliary density perturbation theory is extended to time-dependent perturbations. As its static counterpart, it is based on auxiliary density functional theory in which the Coulomb and exchange-correlation potentials are expressed through one auxiliary function density. As in the case of static perturbations a noniterative alternative to the corresponding coupled perturbed Kohn-Sham method is formulated. The new methodology is validated by local and gradient corrected dynamical polariza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 100 publications
2
37
0
Order By: Relevance
“…Note that the use of auxiliary basis sets in conjunction with the Coulomb norm has a long tradition in DFT methods and is frequently used successfully in various approaches. [59][60][61][62] We now act from left with the resolution-of-the-identity (17) on Eqs. (15) and (16) and additionally insert the resolution-of-the-identity (18) before the potentials v (1) s and v (1) to obtain…”
Section: B Basic Ri-exxrpa Methodsmentioning
confidence: 99%
“…Note that the use of auxiliary basis sets in conjunction with the Coulomb norm has a long tradition in DFT methods and is frequently used successfully in various approaches. [59][60][61][62] We now act from left with the resolution-of-the-identity (17) on Eqs. (15) and (16) and additionally insert the resolution-of-the-identity (18) before the potentials v (1) s and v (1) to obtain…”
Section: B Basic Ri-exxrpa Methodsmentioning
confidence: 99%
“…(5) we introduce an auxiliary basis set, the resolutionof-the-identity (RI) basis set, [67][68][69][70][71] by the unsymmetric resolutions of the identity…”
Section: A Correlation Energy In the Random Phase Approximationmentioning
confidence: 99%
“…Wrong asymptotic behavior of the exchange functional for which local and gradient corrected density approximations are used is believed to be the reason behind the failure of DFT for conjugated systems [25,26]. Contrary to this it has been demonstrated that DFT polarizability calculations of C 60 are in good agreement with CCSD and experimental polarizabilities [27]. This suggests that DFT failures to correctly predict molecular polarizabilities and hyperpolarizabilities are not single sourced, e.g.…”
Section: Introductionmentioning
confidence: 91%
“…However, instead of calculating directly perturbed density matrix elements via the CPKS equation system, perturbed Coulomb fitting coefficients are calculated first in the here used ADPT method [27,29,34,35]. From these perturbed fitting coefficients the perturbed density matrix elements are obtained.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation